E IGFBP-1 upregulates vascular nitric oxide via PI-3-K activation and rescues endothelial function in murine models of insulin resistance. (22nd September 2015) - Rajwani, A; Surr, J; Porter, K E; Viswambharan, H; Imrie, H; Abbas, A; Cubbon, R; Ezzat, V; Kearney, M T; Wheatcroft, S B
Abstract : Background: Low circulating levels of insulin-like growth factor binding protein-1 (IGFBP-1) predict the development of diabetes and cardiovascular disease. Whether IGFBP-1 has direct influences on the vasculature remains unknown however. We previously showed that transgenic over-expression of IGFBP-1 in lean mice conferred favourable effects on endothelial function and blood pressure. We now present data demonstrating that IGFBP-1 increases nitric oxide (NO) production in endothelial cells via PI-3-K activation, and protects against the cardiovascular consequences of insulin resistance in mice. Methods: Male IGFBP-1 transgenic C57Bl/6 mice and littermate controls were challenged by two models of insulin resistance: (i) diet-induced obesity (DIO) and; (ii) crossing with heterozygous insulin receptor knockout mice (IRKO). Cardiovascular function was assessed by tail cuff blood pressure, aortic ser 1177 eNOS phosphorylation following in vivo insulin bolus, and aortic vasomotion ex vivo. Metabolic function was also assessed in DIO mice by insulin- and glucose-tolerance testing, and skeletal muscle Akt 473 phosphorylation following in vivo insulin bolus. To dissect the mechanisms by which IGFBP-1 modulates endothelial function, complementary in vitro studies were conducted with exogenous IGFBP-1. Thus, after incubation with IGFBP-1, we tested vasomotion in intact aorta (organbath), NO generation in HUVECs (citrulline assay) and ser 1177 eNOS phosphorylation in HUVECs (western blot and immunofluorescence). Upstream signalling pathways were further probed using targeted signalling inhibitors. Results: Both DIO and IRKO mice predictably developed endothelial dysfunction and hypertension. In contrast, IGFBP-1 transgenic mice with DIO or IRKO had preserved endothelial function, normal blood pressure, and improved gluco-regulation in DIO despite equal weight gain (see Abstract E table 1 ). In HUVECs and intact aorta, IGFBP-1 induced dose- and time-dependent ser 1177 phosphorylation of eNOS and NO generation via PI-3-K activation. No IGF-I was present in these in vitro assays and these findings were reproducible in vessels with homozygous knockout of the endothelial IGF-receptor, indicating that the actions of IGFBP-1 on the vasculature are independent of IGF-I. Implications: IGFBP-1 improves endothelial function independently of IGF-I and protects against the cardiovascular and metabolic consequences of insulin resistance. Restoration of IGFBP-1 levels may thus be a novel therapeutic target to mitigate cardiovascular risk.